Pedigree structure of American bison (Bison bison) population - Skotarczak, Ewa; Ćwiertnia, Piotr; Szwaczkowski, Tomasz (Czech Journal of Animal Science, 2018)
An effective realization of breeding programs in zoos is strongly determined by completeness of animal pedigree information. The knowledge of pedigree structure allows to maintain optimal genetic variability of a given population. The aim of this study was to estimate the parameters describing the pedigree structure of American bison housed in zoos in the context of further management of the population. Finally, 4269 American bison were analysed (1883 males, 2217 females, and 169 with unknown sex). The registered animals were born between years 1874 and 2013. The following pedigree parameters were estimated: number of fully traced generations, number of complete generations equivalent, index of pedigree completeness, individual inbreeding coefficients, increase of inbreeding for each individual, effective population size, and genetic diversity. The maximum number of fully traced generations was 3 (the mean value is 0.693). The mean inbreeding coefficient for the population studied was 3.26%, whereas individual increase in inbreeding ranged from 0 to 25.12%. Although the pedigree parameters (including the inbreeding level) in the American bison obtained in the present study seem to be acceptable (from the perspective of other wild animal populations), they can be over/underestimated due to incomplete pedigree.
Keywords: relatedness coefficient; captive breeding; genetic diversity; inbreeding